2022
DOI: 10.1186/s41927-022-00316-5
|View full text |Cite
|
Sign up to set email alerts
|

Transitions from pediatric to adult rheumatology care for juvenile idiopathic arthritis: a patient led qualitative study

Abstract: Background Juvenile idiopathic arthritis (JIA) is a childhood autoimmune disease that causes swelling and pain in at least one joint. Young people with JIA experience symptoms that persist into adulthood, and thus will undergo a transition including the o transfer of care from a pediatric rheumatologist an adult rheumatologist. Missing from the literature is research that centres the transition experience of young people with JIA in Canada. This goal of this patient-led research was to explore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Additionally, this follows the Patient and Community Engagement Research approach, 26 which has been used before, [27][28][29] and addresses how individuals with lived experience have a level of understanding others could not. Finally, people who agreed to participate in the study may have been better informed than other Black people living with RA in Canada, more interested in discussing the topics, or more likely to have experienced inequities in health care access and quality of care.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, this follows the Patient and Community Engagement Research approach, 26 which has been used before, [27][28][29] and addresses how individuals with lived experience have a level of understanding others could not. Finally, people who agreed to participate in the study may have been better informed than other Black people living with RA in Canada, more interested in discussing the topics, or more likely to have experienced inequities in health care access and quality of care.…”
Section: Discussionmentioning
confidence: 99%
“…Current approaches regarding the personalized treatment of JIA postulates that complex management should be provided by a multidisciplinary team involving trained physicians, nurses, physiotherapists, psychologists, and other allied health professionals [ 70 ]. The current article questions whether a pediatric cardiologist should become a regular member of the team in order to manage cardiovascular risks in JIA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Jethwa et al reported on a patient-driven pilot survey which collected patient perspectives on telemedicine appointments during the COVID-19 pandemic. Currie et al [ 15 ] shared a patient-led qualitative study in juvenile idiopathic arthritis to help transition from juvenile to adult rheumatology care [ 16 ]. Kee et al and Oyebanjo et al both highlighted PPI in clinical care frameworks.…”
Section: Introductionmentioning
confidence: 99%